2018
DOI: 10.1136/archdischild-2017-314098
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable mortality from respiratory tract infection and sudden unexplained death in children with chronic conditions: a data linkage study

Abstract: The very strong association with chronic conditions suggests that RTI-related mortality may sometimes be a consequence of a terminal decline and not possible to defer or prevent in all cases. Recording whether death was expected on death certificates could indicate which RTI-related deaths might be avoidable through healthcare and public health measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…In the UK, national birth cohorts based on birth registration datasets, with follow-up from linked hospital admission and mortality records are routinely used for research in Scotland [11,12] and Wales [13]. In England, a whole-country birth cohort with rich information about the baby, mother and family could be developed by linking multiple data sources with information about birth and delivery (from Office for National Statistics [ONS] Birth Registration data, National Health Service [NHS] birth notification data, and Hospital Episode Statistics [HES], an administrative hospital dataset), with follow-up via linkage to hospital admission and mortality records.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, national birth cohorts based on birth registration datasets, with follow-up from linked hospital admission and mortality records are routinely used for research in Scotland [11,12] and Wales [13]. In England, a whole-country birth cohort with rich information about the baby, mother and family could be developed by linking multiple data sources with information about birth and delivery (from Office for National Statistics [ONS] Birth Registration data, National Health Service [NHS] birth notification data, and Hospital Episode Statistics [HES], an administrative hospital dataset), with follow-up via linkage to hospital admission and mortality records.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed to determine whether this is due to intercountry differences in the prevalence of chronic conditions, in the provision of healthcare for children with chronic conditions or in the recording of these conditions in hospitalisation records. Further comparison should also include information on what proportion of these deaths were expected (ie, whether RTI was part of terminal decline in child’s health, not possible to prevent) and what proportion were unexpected42.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide clear policy direction in terms of how to prevent childhood deaths: support women before and during pregnancy to improve birth outcomes. We have also demonstrated, using a birth cohort from Scotland, that children with chronic conditions are at increased risk of deaths from respiratory tract infection and, to a lesser extent, sudden unexpected deaths 19. These studies examined mortality in children less than 5 years old.…”
Section: Administrative Datamentioning
confidence: 90%
“…However, since one in four CDOP reviews takes longer than 12 months to complete,11 timeliness of CDOP reviews currently does not appear to be any better than for ONS mortality records. We have previously shown that indicating whether a death is expected would be extremely useful for indicating which deaths are amenable to healthcare intervention 19. Clinician reporting of deaths to CDOP as expected or unexpected could therefore be useful for filtering deaths for CDOP investigation and would provide important information that could be linked to death certificates.…”
Section: Administrative Datamentioning
confidence: 99%